Malignancy and sarcoidosis: A single center experience from Turkey - Esendağlı, Dorina; Köksal, Deniz; Sarınç Ulaşlı, Sevinç; Emri, Salih (Acta Medica, 2023)
Objective: The relationship between cancer and sarcoidosis has been a research topic for a long time. An increased risk of sarcoidosis and sarcoid-like reactions is suggested in patients with malignant disease. The present study aimed to describe the clinical characteristics and the prognosis of 15 Turkish patients who had a diagnosis of both malignancy and sarcoidosis. Methods: The patients admitted to our department between October 2013 and October 2018 were included in this study. Patient data including, the demographic data, clinical, radiological, pathological findings, and applied treatment modalities were retrieved from hospital database. Results: The study included 14 females and 1 male with a mean age of 53.3±11.4 years. Malignancy was the preceding diagnosis in 13 patients. The mean interval time between two diagnoses was 4±3.6 years. Fourteen patients recovered from their cancer, only 1 patient with relapsed NHL was deceased. The most common type of malignancy was breast (n=7) and endometrium (n=3) carcinoma. Surgery was the primary therapeutic modality in 14 patients. Additionally patients received certain drugs which might contribute to onset of sarcoidosis such as Cyclophosphamide (n=8), Adriamycin (n=8), Trastuzumab (n=2), and Rituximab (n=1). Ten patients were asymptomatic for sarcoidosis and 7 patients had stage I pulmonary sarcoidosis. Two third of the patients (n=10) did not receive any therapy for sarcoidosis. Conclusion: This study involves a few number of patients and according to the analysis of this group the presence of malignancy and sarcoidosis in the same patient might promote good prognosis for both entities. However the onset of sarcoidosis during the follow-up period is a challenging clinical condition and a biopsy is needed for differential diagnosis and management decision. Yet the biopsy might not be enough to differentiate between sarcoidosis and the sarcoid reactions related to malignancy. Future studies are needed to enlighten the underlying pathogenesis.